Lament for the Land: On the Impacts of Climate Change on Mental and Emotional Health and Well-Being in Rigolet, Nunatsiavut, Canada - Cunsolo Willox, Ashlee (University of Guelph, 2012)
As the impacts from anthropogenic climate change are felt around the globe, people are increasingly exposed to changes in weather, temperature, wildlife and vegetation patterns, and water and food quality and availability. These changes impact human health and well-being, and resultantly, climate change has been identified as the biggest global health threat of the 21st Century. Recently, the mental health impacts emerging from these changes are gaining increasing attention globally. Research indicates that changes in climate and environment, and the subsequent disruption to the social, economic, and environmental determinants of mental health, are causing increased incidences of mental health issues, emotional responses, and large-scale socio-psychological changes. Inuit in Northern Canada have been experiencing the most rapid climatic and environmental changes on the planet: increased seasonal temperatures; decreased snow and ice quality, stability, and extent; melting permafrost; decreased water levels in ponds and brooks; increased frequency and intensity of storms; later ice formation and earlier ice break-up; and alterations to wildlife and vegetation. These changes are decreasing the ability of Inuit to hunt, trap, fish, forage, and travel on the land, which directly disrupts their health, and is negatively impacting mental and emotional health and well-being. Through a multi-year, exploratory, qualitative case study conducted in Nunatsiavut, Labrador, Canada representing the first research to examine the mental and emotional health impacts of climate change within a Canadian Inuit context, Inuit indicated that climate change was impacting mental health through seven interrelated pathways: strong emotional responses; increased reports of family stress; increased reports of drug and alcohol usage; increased reports of suicide ideation and attempts; the amplification of previous traumas and mental health stressors; decreased place-based mental solace; and land-based mourning due to a changing environment. ...